Intellectual and Aesthetic Relationship between the Public and the Modern Theater (the play Oh Lord!) as a model: فيصل عبد عودة (Al-Academy, 2019)
The issue of the public in the directions and theories of the theater director in the world theater, especially after the emergence of realism and the crystallization of the term direction and the definition of the role of the director in 1850 AD by the Duke Max Mengen took different paths to the Greek, Roman and even Elizabethan audience because it was here subjected to the theatrical equation from its production and presentation due to the fact that the theatrical performance is a technical artistic production, and the audience participation, watching and consumption, and here the participation of the audience was subjected to three directions: the enlightenment in the sense of arousing sense, the incitement in the sense of thinking and criticism, and ritualism in the sense of provoking panic and anxiety. The audience in the modern era is no longer a substitute or representative of the nation as it is for the Greeks and is no longer general, broad representative of various societal groups as it is during the Elizabethan era, so the audience diversified and multiplied depending on the layer of direction treatment and intellectual and aesthetic starting points of the directors. Thus the modern currents exceeded the easy traditional concept of the theatre. The audience entered the game of the play, rather the theater performances created technical determinants that contributed to attracting the theater audience as a participant in the show such as live theater shows, Sun Theater, basement and Café Theater, and open theater. Based on what is presented, the research problem arises in the following question: Since the participation of the audience in the directing process is not new, it has roots that extend to the era of the Greeks, then what are the intellectual and aesthetic ranges taken by this relationship through the new forms of perception and expression of the most prominent international directors who opposed the realistic trend in theater and looked at the relationship between the actor and the receiver with a different view and through the display ( Oh Lord!) as a procedural application